The knowhow book of experiments - Amery, Heather; King, Colin (London ; Tulsa, Okla. : Usborne : EDC, 1977)
Illustrated instructions for a variety of simple experiments that demonstrate basic scientific principles.
4.0
3-6
Keywords: Science -- Experiments -- Juvenile literature; Science -- Experiments; Experiments; Science -- Experiments